Acquisition of Mathematical and Linguistic Skills in Children With Learning Difficulties - Viesel-Nordmeyer, Nurit; Ritterfeld, Ute; Bos, Wilfried (Frontiers in Psychology, 2021)
Comorbid learning difficulties in linguistic and mathematical skills often emerge in primary school age. The cause of coinciding of both learning difficulties during children’s development spanning pre- and primary school age is not yet well understood. To address this research gap, we used data from the German National Educational Panel Study (NEPS; n = 301) of four groups of children which were categorized according to their skill levels in pre-school age: children with learning difficulties isolated in linguistic skills (LD), children with learning difficulties isolated in mathematical skills (MD), children with learning difficulties combined in linguistic and mathematical skills (MD/LD), and children with typical development in both skills (TA). Computing univariate and repeated measures ANCOVAs we compared the mathematical and linguistic development of the four groups of children (LD, MD, LD/MD, TA) spanning age four to ten. Results reveal a partial catch-up in linguistic skills (lexical, grammatical) for children with LD. In contrast, children with MD did not overcome their mathematical competence gap in comparison with TA and LD. Moreover, children with MD showed a decrease in grammatical skills during transition in primary school. Further, children with MD/LD displayed the weakest performance in linguistic and mathematical skills during pre- and primary school age in general. However, after controlling for working memory, initial performance differences between the groups decreased in favor of MD/LD. The relation between linguistic skills and mathematical skills in persisting learning difficulties as well as the specific role of working memory are discussed.